Publish or Perish in Livestock Sciences in Latin American - Martínez, Y. (Cuban Journal of Agricultural Science, 2022)
Nowadays, the scientific-technical information had marked the course for its new and updates spreading in different branches of learning, in turns, the most of scientific advances use specialized journals and the most reliable distribution in order to give path to discoveries (Gretchenko et al. 2018). However, before the Open Science appears, the discoveries were discussed in close spaces or used journals of prestigious recognition, with little access to researchers from developing countries (Abadal 2021).